Peningkatan Hasil Belajar Menguraikan Kosakata Berbagai Jenis Benda Melalui Model Scramble dengan Penguatan Karakter Rasa Ingin Tahu Pada Siswa Kelas I SDN - Lilinggarwati Lilinggarwati; Sutansi Sutansi; Tri Murti (Universitas Negeri Malang, 2022)
Abstract: This study aims to describe the increase in learning outcomes material describing vocabulary through the application of the scramble model by strengthening the character of curiosity in grade 1 students of SDN 1 Kedunglurah, Trenggalek Regency. This study uses a qualitative approach using the type of Classroom Action Research. The results of observations of the average value of student learning outcomes at the pre-action stage is 52.85 with a classical learning completeness of 40.74 percent. In the first cycle the average value of student learning outcomes increased to 66.85 with a mastery of classical learning by 55.55 percent and the value of the percentage of teacher activity and student activity by 85 percent. In cycle II the average value of student learning outcomes increased again to 78.96 with a classical learning completeness of 90.74 percent and the value of the percentage of teacher activity and student activity by 100 percent. Based on the results of the research cycle I and cycle II show that the scramble learning model with the strengthening of curiosity character can improve student learning outcomes material describing vocabulary. Abstrak: Penelitian ini bertujuan untuk mendeskripsikan peningkatan hasil belajar materi menguraikan kosakata melalui penerapan model scramble dengan penguatan karakter rasa ingin tahu pada siswa kelas 1 SDN 1 Kedunglurah Kabupaten Trenggalek. Penelitian ini menggunakan pendekatan kualitatif dengan menggunakan jenis Penelitian Tindakan Kelas. Hasil observasi nilai rata-rata hasil belajar siswa pada tahap pratindakan yaitu 52,85 dengan ketuntasan belajar klasikal sebesar 40,74 persen. Pada siklus I nilai rata-rata hasil belajar siswa mengalami peningkatan menjadi 66,85 dengan ketuntasan belajar klasikal sebesar 55,55 persen dan nilai persentase aktivitas guru dan aktivitas siswa sebesar 85 persen. Pada siklus II nilai rata-rata hasil belajar siswa meningkat lagi menjadi 78,96 dengan ketuntasan belajar klasikal sebesar 90,74 persen dan nilai persentase aktivitas guru dan aktivitas siswa sebesar 100 persen. Berdasarkan hasil penelitian siklus I dan siklus II menunjukkan bahwa model pembelajaran scramble dengan penguatan karakter rasa ingin tahu dapat meningkatkan hasil belajar siswa materi menguraikan kosakata.